Diagnostic Value of High-Sensitivity Troponin T for Subclinical Left Ventricular Systolic Dysfunction in Patients with Sepsis. (24th April 2021) - Hai, Pham Dang; Binh, Nguyen Thanh; Tot, Nguyen Hong; Hung, Ha Manh; Hoa, Le Thi Viet; Hien, Nguyen Viet Quang; Son, Pham Nguyen
Abstract : Background . Left ventricular systolic dysfunction (LVSD) is common in sepsis. Speckle-tracking echocardiography (STE) is a useful emerging tool for evaluating the intrinsic left ventricular systolic function. High-sensitivity cardiac troponin T (hs-cTnT) is the most sensitive biomarker of myocardial injury. However, there are limited data regarding the association between hs-cTnT level and left ventricular systolic dysfunction based on STE in septic patients. We performed this prospective study to evaluate the diagnostic value of hs-cTnT level for subclinical left ventricular systolic dysfunction measured by STE in septic patients according to the sepsis-3 definition. Methods . Patients with sepsis based on sepsis-3 definition admitted to the intensive care unit were prospectively performed STE and hs-cTnT level within 24 hours after the onset of sepsis. Baseline clinical and echocardiographic variables were collected. Left ventricular systolic dysfunction was defined as a global longitudinal strain of   ≥−15%. Results . During a 19-month period, 116 patients were enrolled in the study. The elevated hs-cTnT level was seen in 86.2% of septic patients, and 43.1% of patients had LVSD on STE. The median hs-cTnT level and the proportion of elevated hs-cTnT level (>14 ng/L) were significantly higher in patients with LVSD than in patients without LVSD. The area under the ROC curves of hs-cTnT to detect LVSD was 0.73 (P  < 0.001). In the multivariate analysis, hs-cTnT (HR, 1.002; 95% CI, 1.000 to 1.004; P  = 0.025) and septic shock (HR, 7.6; 95% CI, 2.25 to 25.76; P  = 0.001) were independent predictors of LVSD. Conclusion . Our study indicated that the serum hs-cTnT level might be a useful biomarker for detecting LVSD in septic patients.